2013
DOI: 10.5851/kosfa.2013.33.6.723
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Thawing Methods on the Quality Characteristics of Frozen Beef

Abstract: In this study, the quality characteristics due to the influence of various thawing methods on electro-magnetic and air blast frozen beef were examined. The loin and round of second grade Hanwoo were sliced into 5-7 cm thickness and packed with aerobic packaging. The packaged beef samples, which were frozen by air blast freezing at -45 o C and electro-magnetic freezing at -55 o C, were thawed by 4 thawing methods with refrigeration (4±1 o C), room temperature (RT, 25 o C), cold water (15 o C), and microwave (24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
(16 reference statements)
2
18
0
Order By: Relevance
“…Higher drip losses from broiler chicken breast meat thawed using the microwave method was observed by Oliveira et al [9] as against other thawing methods. Similar values of drip loss in samples thawed using microwave and atmospheric methods were observed by ChwastowskaSiwiecka et al [25] in rabbit meat, as well as by Kim et al [26] in beef and by Kondratowicz et al [27] in pork. Yu et al [28] demonstrated that the amount of thawing leakage is determined by the thawing temperature and increases with rising temperatures.…”
Section: Resultssupporting
confidence: 85%
“…Higher drip losses from broiler chicken breast meat thawed using the microwave method was observed by Oliveira et al [9] as against other thawing methods. Similar values of drip loss in samples thawed using microwave and atmospheric methods were observed by ChwastowskaSiwiecka et al [25] in rabbit meat, as well as by Kim et al [26] in beef and by Kondratowicz et al [27] in pork. Yu et al [28] demonstrated that the amount of thawing leakage is determined by the thawing temperature and increases with rising temperatures.…”
Section: Resultssupporting
confidence: 85%
“…In these samples, microscopic observations showed large spaces within the muscle fibers, whereas these spaces in the magnetically frozen samples were small and scattered throughout the muscle fibers. Kim and others (,b), Ku and others (), and Choi and others () reported reduced total freezing times and improved quality attributes in beef, pork, and chicken samples frozen in a magnetic freezer (ABI Co., Ltd.) at –55 °C compared with samples frozen in an air blast freezer at –45 °C. However, as freezer temperatures were not the same, it is not possible to deduce whether the improvements detected were produced by the MF or by the lower temperature applied.…”
Section: Experimental Data About the Effects Of Mfs On Freezingmentioning
confidence: 97%
“…The user can program different “CAS conditions” (0% to 100% CAS) at the control panel, but the MF intensities and frequencies associated to these “CAS conditions” are not specified. Measurements with devices not usually employed in freezing research (teslameters and oscilloscopes, for example) are needed to correctly describe commercial equipment and, for this reason, many authors do not report these data (Kim and others ,b; Ku and others ; Choi and others ). Therefore, the experimental conditions of assays published in the literature must be analyzed carefully and the results should be treated with caution before drawing conclusions.…”
Section: Experimental Data About the Effects Of Mfs On Freezingmentioning
confidence: 99%
“…Even though the freezing rates achieved in each device were very different, the authors only found minor differences among the samples. By contrast, Kim et al (2013a), Kim et al (2013b), Ku et al (2014), and Choi et al (2015) froze beef, pork, and chicken samples in both a CAS freezer at −55 °C and an air-blast freezer at −45 °C. They concluded that electromagnetic freezing reduced the total freezing times and preserved the quality attributes of the samples better than air-blast freezing.…”
Section: Introductionmentioning
confidence: 93%